Actinomucor elegans and Podospora bulbillosa positively improves endurance to water deficit and salinity stresses in tomato plants - Ahmed Kazerooni, Elham; Maharachchikumbura, Sajeewa S. N.; Al-Sadi, Abdullah Mohammed; Rashid, Umer; Kang, Sang-Mo; Lee, In-Jung (Multidisciplinary Digital Publishing Institute, 2022)
Fungal strains isolated from the rhizosphere of healthy Solanum lycopersicum were examined to mitigate symptoms of drought and salinity stresses. The fungal strains were identified as Actinomucor elegans and Podospora bulbillosa based on their DNA sequencing and morphological analysis. Additionally, the fungal strains were assayed for a number of plant growth promoting traits and abiotic stresses on solid media. Moreover, a greenhouse experiment was conducted and tomato seedlings were treated with 25% PEG or 1.5% NaCl for 12 days, and the impact of plant growth promoting fungi (PGPF) on tomato seedling performance under these conditions was examined. PGPF application raised the survival of the stressed tomato plants, which was evidenced by higher physiological and biochemical processes. The PGPF-inoculated plants exhibited higher chlorophyll, carotenoid, protein, amino acid, antioxidant activities, salicylic acid, glucose, fructose, and sucrose contents, and showed lower hydrogen peroxide, and lipid metabolism relative to control plants under stress. Analysis using gene expression showed enhanced expression of SlF3H gene and reduced expression of SlNCED1, SlDEAD31, SlbZIP38, and SlGRAS10 genes following PGPFs application. Overall, the outcomes of this study elucidate the function of these fungal strains and present candidates with potential implementation as biofertilizers and in promoting plant stress endurance.